PERAN PENDIDIKAN KEWARGANEGARAAN DALAM MEMBANGUN EMPATI DAN MENCEGAH POLARISASI SOSIAL DI KALANGAN GENERASI Z - Fathiril Haq (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
Social polarization among Generation Z, particularly in digital spaces, has emerged as a pressing issue in recent years. This study aims to explore how Civic Education can serve as a preventive strategy to foster empathy and reduce polarization within this generation. Using a descriptive qualitative approach through literature review, the research analyzes 17 scholarly articles focusing on Civic Education, social empathy, polarization, and Generation Z. The findings reveal that conventional Civic Education practices are often normative and disconnected from contemporary social realities. However, when Civic Education is implemented through participatory, contextual, and reflective learning strategies especially when integrated with digital literacy it becomes more effective in developing critical awareness, empathy, and social solidarity among students. The study concludes that Civic Education plays a vital role not only in transmitting civic values but also in shaping inclusive and empathetic future citizens who are resilient to polarization in a fragmented digital era.